Advancing maritime technology: Evaluating situation awareness support systems for engine room monitoring at the future shore control centre - Han, Changhun; Islam, Rabiul; Abeysiriwardhane, Apsara; Chai, Shuhong (Journal of international maritime safety, environmental affairs, and shipping, 2024)
Remote operation offers promising advantages as a viable transitional phase toward autonomous ships, but at the same time, it introduces new challenges in maintaining situation awareness. However, situation awareness is misunderstood as an essential construct for only navigational tasks, albeit situation awareness issues are recurrently reported during system monitoring, e.g. power plants. Hence, this within-subjects study developed the two situation awareness support systems for engine room monitoring based on information requirements and schema instantiation. Sixteen marine engineers participated in the four simulation experiments, and their objective and subjective situation awareness, fault detection rate, response speed and change blindness were evaluated. The findings describe that presenting a few critical perception elements for comprehension is promising to mitigate interface complexity and enable efficient pattern matching. However, caution is necessary for selecting the means of access to elements of low importance, as it can induce attentional tunnelling and additional cognitive load, which can devastate the situation awareness and fault-detecting performance when compounded by high cognitive load from primary monitoring tasks. This study recommends entailing the current level of situation awareness, cognitive load and stress into the support system design to determine the extent and timing of assistance for varying operational demands.